The Power Consumption Performance of an Orbiting Screw Solid-Solid Mixer - Senda, Semuel Pati; Renanto, Renanto; Roesyadi, Achmad; Sumaryono, Wahono; Bindar, Yazid (ITB Journal Publisher, LPPM ITB, 2012)
In this work we have investigated mixing in a modified orbiting screw mixerÂ (MOSM)Â designedÂ forÂ solid-solid mixing.Â MixingÂ wasÂ carriedÂ outÂ using urea powder and natural zeolite powder (UZ) of three varying particle sizes (50-60, 60-80 and 80 mesh). Power consumption was calculated from the measured torque of orbit and screw, obtained from computerized records. It was found that theÂ mixingÂ processÂ inÂ theÂ modifiedÂ orbitingÂ screwÂ mixerÂ withÂ airÂ injection required a lower power consumption for each particle-size group when compared to mixing without air injection. With UZ mixing in MOSM withÂ air injection, the lowest E was obtained forÂ the 60-80 mesh particle-size groupÂ (4,297 Joule/kg-1),whereas when mixing withoutÂ air injection, the value wasÂ 10,296 J/kg. The best mixingÂ operation in this experiment was achieved at NFrÂ =Â 1.18x10-3 and in the rangeÂ ofÂ valuesÂ NReâÂ 8.77x107 toÂ 2.63x108.Â Moreover,Â in thisÂ study,Â weÂ have developedÂ anÂ equationÂ toÂ estimate theÂ powerÂ consumption requiredÂ forÂ mixing and determined its correlation with dimensionless numbers.